Aboriginal cosmotechnics - Simon Sadler (Footprint)
The unassuming title of the 2021 Australian book Design: Building on Countrypositions Aboriginal making as potentially cosmotechnical, since it restores the inter-dependence of what in the west would be categorised as nature, culture, technology. As the editor of the series to which the book belongs reminds us, ‘in the Aboriginal worldview, everything starts and ends with Country. ... Everything is part of a continuum, and endless flow of life and ideas emanating from Country’ which ‘includes the built environment and objects, which reflects both a conceptual and a physical process with ancestral and cultural dimensions’.And yet colonisation of the continent all but erad-icated Country as it had evolved over 65 000 years. So having carefully pieced together the objects, spiri-tuality, camps, shelters, materials and kinship of what Aboriginal design was (and is, in isolated ways), the book posits something more synthetic – an ‘offering’, as its conclusion graciously puts it, in which ‘this new Australian design will improve the wellbeing of people and create places that ultimately mean more to all of us. It will extend Country, not abrogate it, and it should be created with that in mind – because we are all con-nected to Country’.